2005
DOI: 10.1091/mbc.e05-02-0096
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-Trisphosphate Signaling Regulates Mating Behavior inCaenorhabditis elegansMales

Abstract: Complex behavior requires the coordinated action of the nervous system and nonneuronal targets. Male mating in Caenorhabditis elegans consists of a series of defined behavioral steps that lead to the physiological outcomes required for successful impregnation. We demonstrate that signaling mediated by inositol 1,4,5-trisphosphate (IP 3 ) is required at several points during mating. Disruption of IP 3 receptor (itr-1) function results in dramatic loss of male fertility, due to defects in turning behavior (durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…The defect in male fertility of shn-1(tm488) mutant was comparable to that of itr-1(sa73)(lf) mutant. As previously described, the itr-1(sa73)(lf) mutant showed a severe male fertility defect (Gower et al, 2005). Taken together, these results suggest that shn-1 is essential for both hermaphrodite and male fertility in C. elegans.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The defect in male fertility of shn-1(tm488) mutant was comparable to that of itr-1(sa73)(lf) mutant. As previously described, the itr-1(sa73)(lf) mutant showed a severe male fertility defect (Gower et al, 2005). Taken together, these results suggest that shn-1 is essential for both hermaphrodite and male fertility in C. elegans.…”
supporting
confidence: 84%
“…Male mating behaviors are composed of a series of steps: hermaphrodite recognition, backing, turning, vulval location and copulation. We specifically examined the male turning behavior of shn-1 males since it has been described that itr-1 plays important roles in mating especially in male turning behavior (Gower et al, 2005). Similarly most of our studies also show the genetic relation of itr-1 and shn-1.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…MAB-23 is a DM domain transcription factor necessary for the differentiation of sexspecific tissues, and mab-23 males are unable to adopt the appropriate turning posture because of a diagonal muscle differentiation defect (Lints and Emmons, 2002). The IP 3 receptor gene itr-1 is expressed in CP8/9, and diagonal muscles and itr-1 mutant males also exhibit the wide-turn and late-turn phenotypes (Gower et al, 2005). Hence, the "ray sensorimotor circuit" is one element required for copulatory turning (Fig.…”
Section: The Neuronal Regulation Of Male Sexual Turning Behaviormentioning
confidence: 99%
“…Although EGL-8 is expressed in most of the neurons of the worm, it is also expressed in the posterior intestine (Lackner et al 1999;Miller et al 1999). Recent studies have also indicated that EGL-8 functions in pharyngeal pumping, sperm transfer, and Ca 21 oscillation-associated posterior body contractions of the intestine, suggesting that it may function in nonneuronal tissues (Bastiani et al 2003;Steger and Avery 2004;Espelt et al 2005;Gower et al 2005). Whether or not EGL-8 feeds into the ERK/MAP kinase cascade or acts in a parallel pathway remains to be determined.…”
mentioning
confidence: 99%